Mirtis kaip virsmas kinų filosofinėse-religinėse tradicijose. - Poškaitė, Loreta (Problems / Problemos, 2025)
The article investigates the Chinese concept of death from the perspective of cosmic transformations (hua..., bian ...), which is almost exceptionally explored only in the studies of its understanding in the classical Daoist thought. The article argues that the view of death as transformation is no less important to other Chinese philosophical-religious traditions, namely, Classical and later (neo-)Confucianism, as well as a 'local' religion and Daoist alchemist tradition; thus, it could be considered as revealing the peculiarity and complexity of a general Chinese understanding of death. Such complexity is comprised by the polysemanticity of the very term 'transformation', stemming from Chinese processual ontology and emanative-recreative-generative (sheng sheng ...) cosmogony. The article examines the views of death, as well as their development, co-relation and change according to two aspects -- or 'paradigms' -- of transformation -- the one of human 'souls' (hun-po) and of body/forms (xing ...), with the extension of a historical perspective from Classical Confucianism and Daoism (the texts Lunyu, Yijing, Liji, Laozi, Zhuangzi) to Neo-Confucian Zhu Xi and the ideas of Daoist alchemists. It also includes the concept of a dual soul (or souls) in Chinese local religion, formed in the pre-imperial period and later incorporated into the teaching of the latter (Daoist alchemy and Zhu Xi's thought). The analysis is concentrated on the co-relation and comparison of insights on death from those various sources, as well as their relation to ontological and cosmological terms yin-yang ..., dao ..., qi ..., and sheng sheng ....